2022
DOI: 10.1111/eci.13910
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of cerebrospinal fluid biomarkers in Alzheimer's disease

Abstract: Background Alzheimer's disease (AD) is a complex disease that shares clinical features with other dementias. It is important to establish a specific and reliable diagnosis. Nowadays, AD diagnosis is based on cerebrospinal fluid (CSF) biomarkers. However, the corresponding cut‐offs differ amongst studies. This study aims to evaluate the CSF biomarkers in the AD differential diagnosis. Methods Clinical relevant biomarkers (amyloid β42 (Aβ42), t‐Tau, p‐Tau, amyloid β40 (Aβ40), neurofilament light chain (NfL)) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…As mentioned previously, previous reports have shown that declines in p-tau levels and t-tau protein concentrations in the cerebral fluid of AD patients were not altered in a statistically significant way. In contrast, no significant longitudinal changes in p-tau and t-tau were found in the authors’ assay ( Lleo et al, 2019 ; Pena-Bautista et al, 2023 ).…”
Section: Biomarkers Of Alzheimer’s Diseasementioning
confidence: 67%
See 3 more Smart Citations
“…As mentioned previously, previous reports have shown that declines in p-tau levels and t-tau protein concentrations in the cerebral fluid of AD patients were not altered in a statistically significant way. In contrast, no significant longitudinal changes in p-tau and t-tau were found in the authors’ assay ( Lleo et al, 2019 ; Pena-Bautista et al, 2023 ).…”
Section: Biomarkers Of Alzheimer’s Diseasementioning
confidence: 67%
“…Aβ exists mainly as Aβ40 and Aβ42 subtypes, and under normal conditions, the production and clearance of Aβ40 is in dynamic balance; Aβ42 is neurotoxic and accumulates in AD sufferers’ brains to produce senile plaques, showing good accuracy in detecting AD ( Hansson et al, 2018 ). Pena-Bautista et al (2023) statistically found decreased concentrations of Aβ42 in the CSF of those with AD, and lower CSF Aβ42 concentrations distinguished AD patients from healthy controls. Different illness conditions had different amounts of Aβ42 in the CSF, and AD could be distinguished from other forms of dementia based on the levels of Aβ42.…”
Section: Biomarkers Of Alzheimer’s Diseasementioning
confidence: 80%
See 2 more Smart Citations
“…The CSF samples were analyzed by chemiluminescence (CLIA) immunoassay (Lumipulse ® Fujirebio, Japan) in the clinical diagnosis service from Hospital La Fe. The cut-off values used for each biomarker were (reference level) >830 pg mL −1 for Aβ42, <380 pg mL −1 for t-Tau, <60 pg mL −1 for p-Tau181, >0.069 Aβ42/Aβ40, <0.41 t-Tau/Aβ42, and <810 pg mL −1 for NfL [ 74 ].…”
Section: Methodsmentioning
confidence: 99%